Development of New Antidiabetic Drink from Sargassum sp.: Total Phenolic Content, α-Glucosidase Inhibition, and Sensory Analysis - Umam, Nada Itorul; Mariana, Rina Rifqie; Gunawan, Aditia Gustiana; Prihanto, Asep Awaludin; Muyasyaroh, Hidayatun (Universitas Ahmad Dahlan, 2025)
Diabetes is a major global health challenge, with α-glucosidase inhibitors playing a key role in managing blood glucose levels by delaying carbohydrate digestion and absorption. This study developed an antidiabetic functional drink combining Sargassum extract with cinnamon (Cinnamomum burmannii) and temulawak (Curcuma xanthorrhiza). A Completely Randomized Design (CRD) was used with four treatments: a control (F0) and formulations with 15% (F1), 17.5% (F2), and 20% (F3) Sargassum extract. Data on pH, polyphenols, and α- glucosidase inhibition were analyzed using ANOVA, while sensory attributes were evaluated with nonparametric tests. The addition of Sargassum extract from 15% to 17.5% significantly increased the phenolic content by 15%. However, it did not affect α-glucosidase inhibition. This suggests that not all phenolic compounds in Sargassum contribute to the inhibition of α-glucosidase. The formulation with 20% Sargassum, 15% cinnamon, and 18.5% temulawak extract exhibited the highest phenolic content (315.21 mg GAE/100 ml) and α-glucosidase inhibition (62.27%). The sensory analysis shows that adding up to 20% Sargassum is still acceptable for the panelists, with a hedonic value of 3.34 to 3.43 (neutral). This study discovers that the bitterness of Sargassum at the highest concentration can be mitigated by adding cinnamon and temulawak without reducing the antidiabetic potential. These results contribute to conveying the potential of this drink as a natural anti-diabetic product with good sensory acceptability. Further research is needed to evaluate bioactive interactions and phenolic composition to optimize efficacy.